Professor G. W. Leitner in England: The Oriental Institute, Woking Mosque, Islam and Relations with Muslims, 1884–1899. Issue 1 (2nd January 2021) - Gilham, Jamie
ABSTRACT: This article examines in detail for the first time the later life and work of the Orientalist G. W. Leitner (1840–1899), who retired from Indian government service and settled permanently in England in the 1880s. It explains why Leitner devoted the last years of his life to creating an ambitious Oriental Institute in Woking, Surrey, which included the first purpose-built mosque in Britain. It also considers why and how Leitner went against convention to publicly explain and defend aspects of Islam and Muslim culture, most famously in his 1889 lecture and pamphlet entitled 'Muhammadanism'. It reveals, however, that Leitner's imperialist outlook and preoccupation with class and caste drew him into conflict with some of the leading Muslims in late-Victorian Britain, and argues that his interaction with them exposed the limitations of his Christian charity and benevolence.